Retinoic acid receptors' expression and function during zebrafish early development - Oliveira, Eva (2018)
Retinoic acid (RA) regulates many developmental processes through its binding to two types of nuclear receptors, the retinoic acid receptor (RAR), and the retinoid-X receptor (RXR), which preferentially binds to the 9-cis isomer. Here we analyzed the RAR/RXR regulatory system during the first 5 days of development of zebrafish. Analysis of the relative transcript abundances for the four RAR and the six RXR zebrafish genes present in the zebrafish genome indicates a transition from maternal to embryonic transcripts during the first 24 h post fertilization. These changes did not affect the response to exogenous RA of the known RAR-responsive genes cyp26a1, dhrs3a, hoxb1b, hoxb5a, and hoxb5b. At the transcriptomic level, RA treatment elicited a negative feedback of genes involved in the endogenous RA synthesis and reduced levels of transcripts related to organ and anatomic development. These effects occurred at concentrations at which no morphological changes were observed. Data analysis suggests that exposure to exogenous RA results in an advance of the developing program, activating genes that should remain silent until later developmental stages and inhibiting expression of development-related genes. We conclude that zebrafish embryos are particularly sensitive to potential disruptors of the RAR/RXR regulatory system.